MANAJEMEN STRATEGIK DALAM KAJIAN MANAJEMEN PENDIDIKAN ISLAM - Abra, Nabil Aisar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In this modern era, many educational institutions have been established and are also competing with each other to get consumers or students to enter their institutions, so a strategy is needed to be able to sell their institutions and be able to recruit many students. The purpose of this research is to study Red Ocean and Blue Ocean strategies in educational institutions. The type of research used in this article is library research where researchers collect books and articles related to the title of this article. The results of the research are that in the management of Islamic education, Red Ocean and Blue Ocean Strategy can be important references in planning strategies and managing educational institutions. The Red Ocean Strategy can help educational institutions compete in a saturated market by emphasizing operational efficiency and improving service quality. Meanwhile, the Blue Ocean Strategy can help educational institutions to create new markets by developing innovative ideas and offering added value that is different from the existing ones. These two strategies can help Islamic educational institutions to maintain their competitive advantage and improve their performance in an increasingly competitive and dynamic market. Therefore, it is important for educational institutions to consider the right strategy to achieve goals